Prevalence of Asymptomatic Bacteriuria Among Pregnant Women Attending a Tertiary Care Hospital in Western India - Patel, Paresh; Patel, Manish; Desai, Khanjan (National Journal of Community Medicine, 2022)
Introduction: Asymptomatic bacteriuria refers to the presence of bacteria in urine having overall incidence during pregnancy ranges between 2%-10%. The study was conducted to assess prevalence of asymptomatic bacteriuria in pregnant women. The study also aimed to find out the most common Pathogenic organism isolates from urine sample. Methodology: Pregnant women with varying gestational periods attending the tertiary care hospital without any symptoms of UTI were included in the study. Their urine was tested for routine microscopy, culture, and certain biochemical testing. Results: Prevalence rate of asymptomatic bacteriuria was seen 13.8% in pregnant women. Proportion of asymptomatic bacteriuria is highest 14.70% in age group 26-30 year, 23.33% in first trimester. Both gram negative and gram-positive bacteria were isolated, but gram-positive cocci isolates were higher comparatively gram-negative bacilli. Organisms recovered in order of frequency were E. coli, Coagulase Negative Staphylococci (CONS), S. aureus, Klebsiella spp, Acinetobacter spp, Citrobacter spp and Enterobacter spp. Conclusion: High prevalence of asymptomatic bacteriuria demands routine bacteriological screening of pregnant women. This will help in early treatment of asymptomatic bacteriuria which will help in prevention of acute and chronic pyelonephritis.